A novel LNG/O2 combustion gas and steam mixture cycle with energy storage and CO2 capture. (1st February 2017) - Chen, Yaping; Zhu, Zilong; Wu, Jiafeng; Yang, Shifan; Zhang, Baohuai
Abstract: A gas and steam mixture cycle (GSMC) is presented with a mixture of LNG/O2 (liquid natural gas/oxygen) combustion product and feedwater as working medium, integrating features of high efficiency power generation, peak shaving, energy storage and CO2 capture. The liquefied oxygen is produced during off-peak hours. During the operation hours, the cryogenic liquids of both LNG and oxygen are pumped to a high pressure and preheated before entering the combustors through the burners. The combustion product heats and mixes with the atomized feedwater to form supercritical H2 O/CO2 mixture vapor for power generation in a turbine unit. The CO2 vapor is separated from condensate water in the condenser and liquefied by the cryogenic liquids of both LNG and oxygen after being compressed to a higher pressure. The circulation feedwater is injected to the annular channel between flame tube and shell cylinder of modular combustor via feedwater heating system. The results show that under the conditions of turbine inlet parameters of 40 MPa/800 °C and condensation temperature of 30 °C, the output power efficiency based on the thermal value of LNG fuel is 49.2% and the equivalent net efficiency is 46.4%, which accounts for 1/4 off-peak electricity consumption for liquid O2 production. Highlights: A gas and steam mixture cycle (GSMC) is presented with H2 O and CO2 as working medium. GSMC has high efficiency power generation, energy storage and CO2 capture features. Modular combustors without stack replaces boiler with zero CO2 and NOx emissions. Output power efficiency is 49.2% under turbine inlet/outlet of 40 MPa/800 °C and 30 °C. Equivalent net efficiency is 46.4% under same conditions accounting 1/4 ASU power.